Enamel–dentine junction morphology reveals population replacement and mobility in the late prehistoric Middle Nile Valley - Nicolas Martin; Adrien Thibeault; Lenka Varadzinová; Donatella Usai; Stanley H. Ambrose; Daniel Antoine; Petra Brukner Havelková; Matthieu Honegger; Joel D. Irish; Friederike Jesse; Laura Maréchal; Marta Osypińska; et al. (Proceedings of the National Academy of Sciences, 2025)
Transitions from foraging to food-production represent a worldwide turning point in recent human history. In the Middle Nile Valley this cultural shift occurred between the sixth and beginning of the fifth millennium BCE. Significant craniodental morphological differences remain inadequately tested by biometric analyses of ancestry and may reflect population origins or diet change between the last hunter-fisher-gatherers (Mesolithic) and first food-producers (Neolithic). Moreover, with no ancient DNA data for this region and very few morphological studies including large samples of Mesolithic individuals, the late prehistoric population history of the Nile Valley remains unclear. Here, we present enamel–dentine junction (EDJ) morphological analyses (based on X-ray microtomography) and biological affinities for 88 individuals spanning 14,000 y from Sudan and southern Egypt. Significant EDJ morphological differences between the last foragers and first food-producers suggest major biological discontinuity at the Neolithic transition. Nevertheless, the persistence of the earlier forager population in the Sudanese Eastern Sahara indicates settlement and population replacement mainly along the Nile. We also present biological evidence of interaction and mobility between these contemporaneous populations during the middle Holocene in the region. It supports the phylogenetic value of EDJ morphology for investigating population affinities at a microevolutionary scale. These results yield insights into the deep population history of the Nile Valley. They provide firm evidence for population replacement and migration toward the region at the onset of the Neolithic transition, attesting that these key changes were not solely triggered by cultural diffusion and diet change.